Le comportement des salaires chez les travailleurs syndiqués de l’industrie de la construction au Canada - Rabeau, Yves (L'Actualité économique, 1981)
ABSTRACTIn this paper, we analyze the behaviour of wages of the unionized workers of the construction industry in Canada. We compare the behaviour of construction wages to those observed in the sectors exposed to and protected from international competition. One conclusion of our analysis is that the construction sector is by far the most inflationnary sector of the Canadian economy. Union power in the construction industry combined with the control of labour supply by skilled trades associations in a market which lends itself to bilateral oligopoly can thus lead to wage increases in the construction sector which in the current inflationnary context exceed those in all other sectors of the economy. This situation is possible because construction firms do not have to face the threat of international competition. The result of this situation is to reduce the level of activity and employment in the construction sector. In addition, the mechanism for fixing wages serves to accentuate the cyclical fluctuations in the construction sector.